Extensions of the stone duality to the category of Boolean spaces and continuous maps. Issue 7 (3rd July 2022) - Dimov, G.; Ivanova-Dimova, E.
Abstract: Using our results from [4], we present a new proof of the extension of the Stone duality theorem to the category BooleSp of zero-dimensional locally compact Hausdorﬀ spaces (= Boolean spaces) and continuous maps that was provided by Dimov [3], and obtain two new duality theorems for the category BooleSp .